A Single Measure of Overall Export Performance. (August 2022) - Chakrabartty, Satyendra Nath; Sinha, Deepankar
Exports are a lifeline to a country's growth, and an overall index can describe its export performance. However, there is little evidence of a single measure encompassing all the relevant aspects of exports. A composite and multi-dimensional measure can aid in assessing the relative position of a country in the world list and identifies necessary policy interventions. The article proposes an Overall Export Performance Index that satisfies the principles of index formation—monotonicity, time reversal, robustness and an unbiased approach. The proposed index avoids selecting weights and scaling variables. It facilitates the identification of crucial indicators requiring the attention of policymakers, tracking the progress of a country across time and the computing of mean and variance of the index for a group of countries at a given time. An empirical comparison of the USA and India reveals that India registered better overall export performance than the USA from 2015 to 2018. The results suggest India's need for reforms in existing foreign trade policies. JEL Codes: F1, F10, F13